Injury of the Mammillothalamic Tract in Patients with Thalamic Hemorrhage - Kwon, Hyeok Gyu; Lee, Han Do; Jang, Sung Ho (Frontiers in Human Neuroscience, 2014)
Objective: Injury of the mammillothalamic tract (MTT) has been suggested as one of the plausible pathogenic mechanisms of memory impairment in patients with thalamic hemorrhage; however, it has not been clearly demonstrated so far. We attempted to investigate whether injury of the MTT documented by diffusion tensor tractography following thalamic hemorrhage correlates with cognitive impairment. Methods: We recruited 22 patients with a thalamic hemorrhage and 20 control subjects. MTTs were reconstructed using the probabilistic tractography method. Patients were classified into two subgroups: reconstructed group, patients whose MTT was reconstructed in the affected hemisphere, and non-reconstructed group, patients whose MTT was not reconstructed. Results: Mammillothalamic tract was reconstructed in 5 (22.7%, reconstructed group) patients in the affected hemisphere and was not reconstructed in the remaining 17 patients (77.3%, non-reconstructed group). In addition, the MTT was not reconstructed even in the unaffected hemisphere in four patients (23.5%) in non-reconstructed group. Fractional anisotropy and mean diffusivity values of the affected hemisphere in reconstructed group also did not show significant differences from those in the unaffected hemisphere of reconstructed group and the control group (p > 0.05). However, the tract volume of the affected hemisphere in reconstructed group was significantly lower than that of the unaffected hemisphere in reconstructed group and the control group (p < 0.05). Conclusion: A large portion of patients with thalamic hemorrhage appeared to suffer severe injury of the ipsilesional MTT (77.3%) and 18.2% of them appeared to suffer severe injury even in the contralesional MTT. In addition, the remaining 22.7% of patients who had preserved integrity of the ipsilesional MTT appeared to suffer partial injury of the ipsilesional MTT.